Prediction of necrotizing enterocolitis in very low birth weight infants by superior mesenteric artery ultrasound of postnatal day 1: A nested prospective study - Yue, Guang; Wang, Jun; Yang, Sheng; Deng, Ying; Wen, Yang; Jia, Wen; Cao, Huiling; Ju, Rong; Shi, Yuan (Frontiers in Pediatrics, 2023)
Background: Necrotizing enterocolitis (NEC) is a devastating intestinal complication that occurs mainly in very-low-birth-weight infants (VLBWI). The study`s aim was to investigate the possibility of early prediction of NEC on postnatal day 1 based on superior mesenteric artery (SMA) doppler ultrasonograpy. Methods: A prospective, observational, nested case control study (ChiCTR1900026197) was conducted to enroll VLBWIs (birth weight <1,500 grams) between October 2019 and September 2021. Doppler ultrasound measurement was done during the first 12 hours of life and before first feeding. Infants developing NEC (stage Ⅱ or Ⅲ) subsequently were included in NEC group and infants spare of NEC were included in control group. Results: 370 VLBWIs were enrolled (30 NEC cases). Among the ultrasound parameters, S/D was significantly higher in the NEC group (OR 2.081, 95%CI 1.411-3.069, P=0.000). The area under the receiver operating curve (AUROC) following the Logistic regression was 0.704 (95%CI 0.566-0.842, P=0.001). The sensitivity of S/D for predicting NEC was 52.2% and the specificity was 92.7%. The critical value of S/D was 6.944 and Youden index was 0.449. Preplanned subgroup analysis confirmed that NEC infants of different stages were characterized by different SMA bloodstream. Small for gestational age (SGA) might be a confounding factor affecting intestinal bloodflow. And infants with delayed initiation or slow advancement of feeding exhibited characteristic intestinal perfusion. Conclusions: In VLBWI, early SMA ultrasound shows the potential to predict NEC. It is reasonable to speculate that SMA bloodstream is related to intestinal structural and functional integrity.